2006
DOI: 10.1007/s00203-006-0199-0
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles of bacterial antagonists inhibit mycelial growth of the plant pathogen Rhizoctonia solani

Abstract: Bacterial antagonists are bacteria that negatively affect the growth of other organisms. Many antagonists inhibit the growth of fungi by various mechanisms, e.g., secretion of lytic enzymes, siderophores and antibiotics. Such inhibition of fungal growth may indirectly support plant growth. Here, we demonstrate that small organic volatile compounds (VOCs) emitted from bacterial antagonists negatively influence the mycelial growth of the soil-borne phytopathogenic fungus Rhizoctonia solani Kühn. Strong inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
270
2
10

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 381 publications
(291 citation statements)
references
References 52 publications
9
270
2
10
Order By: Relevance
“…Although other studies have shown that from 30 to 60 % of isolates of soil bacteria can produce volatile fungal inhibitors (Zou et al, 2007) and that these bacteria come from very diverse genera, including Bacillus, Micrococcus, Rhizobium, and Xanthomonas (Kai et al, 2007;Zou et al, 2007), this was not observed in our experiments. Hartmann et al (2009) pointed out that the inhibitory capacity of a compound in the soil will depend not only on its specific biochemical effects on a pathogen but also on the ability of the compound to diffuse in the culture media or soil.…”
Section: Antibiosis Testscontrasting
confidence: 79%
“…Although other studies have shown that from 30 to 60 % of isolates of soil bacteria can produce volatile fungal inhibitors (Zou et al, 2007) and that these bacteria come from very diverse genera, including Bacillus, Micrococcus, Rhizobium, and Xanthomonas (Kai et al, 2007;Zou et al, 2007), this was not observed in our experiments. Hartmann et al (2009) pointed out that the inhibitory capacity of a compound in the soil will depend not only on its specific biochemical effects on a pathogen but also on the ability of the compound to diffuse in the culture media or soil.…”
Section: Antibiosis Testscontrasting
confidence: 79%
“…This result is in agreement with previous findings [52] where 76.59% decrease in S. sclerotiorum growth is obtained using volatile organic compounds. B. subtilis is able to produce volatile elements exhibiting antifungal activity toward R. solani and B. cinerea [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Certain bacteria are considered as beneficial, because they produce phytohormones (Azospirillum and Pseudomonas) (Mantelin and Touraine, 2004;Preston, 2004) and antifungal compounds (Stenotrophomonas, Pseudomonas and Microbacterium) (Preston, 2004;Kai et al, 2007;Zachow et al, 2008) or contribute to biogeochemical cycling of sulphur (Acidovorax) (Schmalenberger and Kertesz, 2007) or nitrogen, as diazotrophs and denitrifiers (Azospirillum) (Costacurta and Vanderleyden, 1995). Bacteria considered as human opportunistic pathogens, such as Stenotrophomonas maltophilia, Enterobacter cloacae (Berg et al, 2005) or vine phytopathogenic bacteria, such as Xylophilus ampelinus (Grall and Manceau, 2003), were able to assimilate root exudates and to proliferate in the rhizosphere of different plant species.…”
Section: Root Exudate Assimilationmentioning
confidence: 99%